Advances in Structural Integrity Proceedings of SICE 2016 (Springer Singapore, 2018)
This book includes selected technical papers presented at the First Structural Integrity Conference and Exhibition (SICE-2016). The papers, by eminent scientists and academicians working in the areas of structural integrity, life prediction, and condition monitoring, are classified under the domains of: aerospace, fracture mechanics, fatigue, creep-fatigue interactions, civil structures, experimental techniques, computation mechanics, polymer and metal matrix composites, life prediction, mechanical design, energy and transport, bio-engineering, structural health monitoring, nondestructive testing, failure analysis, materials processing, stress corrosion cracking, reliability and risk analysis. The contents of this volume will be useful to researchers, students and practicing engineers alike. .